The tiny Hairless protein from Apis mellifera: a potent antagonist of Notch signaling in Drosophila melanogaster. - Maier, D.; Chen, A.X.; Preiss, A.; Ketelhut, M. (BMC Evolutionary Biology, 2008)
The Notch signaling pathway is fundamental to the regulation of many cell fate decisions in eumetazoans. Not surprisingly, members of this pathway are highly conserved even between vertebrates and invertebrates. There is one notable exception, Hairless, which acts as a general Notch antagonist in Drosophila. Hairless silences Notch target genes by assembling a repressor complex together with Suppressor of Hairless [Su(H)] and the co-repressors Groucho (Gro) and C-terminal binding protein (CtBP). Now with the availability of genomic databases, presumptive Hairless homologues are predicted, however only in insect species. To further our understanding of Hairless structure and function, we have cloned the Hairless gene from Apis mellifera (A.m.H) and characterized its functional conservation in Drosophila.The Apis Hairless protein is only one third of the size of the Drosophila orthologue. Interestingly, the defined Suppressor of Hairless binding domain is interrupted by a nonconserved spacer sequence and the N-terminal motif is sufficient for binding. In contrast to Apis Hairless, the Drosophila orthologue contains a large acidic domain and we provide experimental evidence that this acidic domain is necessary to silence Hairless activity in vivo. Despite the dramatic size differences, Apis Hairless binds to the Drosophila Hairless interactors Su(H), Gro, CtBP and Pros26.4. Hence, Apis Hairless assembles a repressor complex with Drosophila components that may have a different topology. Nevertheless, Apis Hairless is sufficient to repress the Notch target gene vestigial in Drosophila. Moreover, it is able to rescue Hairless mutant phenotypes, providing in vivo evidence for its function as a bona fide Notch antagonist.This is the first interspecies-complementation analysis of the Hairless gene. Guided by evolutionary comparisons, we hope to eventually identify all the relevant structural domains and cofactors of Hairless, thereby opening an avenue for further insights into the repressor-complexes that down-regulate Notch signaling also in other, higher eukaryotes.